Intensive Blood Pressure Control in Patients With Diabetes and Previous Stroke: A Post‐Hoc Analysis of ACCORD‐BP Trial - Zhixian Wang; Jue Wang; Liu He; Chao Jiang; Yufeng Wang; Ting Shen; Meiqi Zhao; Enze Li; Ning Zhou; Caihua Sang; Xin Du; Jianzeng Dong; et al. (The Journal of Clinical Hypertension)
ABSTRACT Intensive systolic blood pressure (SBP) control reduces cardiovascular outcomes in hypertensive patients, but its effects in those with diabetes and prior stroke need further evidence. Among 4733 patients with elevated SBP enrolled in the ACCORD‐BP (Action to Control Cardiovascular Risk in Diabetes–Blood Pressure) trial, this post‐hoc analysis focused on 307 patients with type 2 diabetes and prior stroke to evaluate intensive versus standard SBP control. The primary outcome was major adverse cardiovascular events (MACE), a composite of cardiovascular death, nonfatal myocardial infarction, or nonfatal stroke. Inverse probability of treatment weighting (IPTW)‐adjusted Kaplan‐Meier and Cox regression analyses were performed with a 3‐year conditional landmark. Multivariable Cox regression models and overlap weighting models were constructed in sensitivity analysis. In landmark analysis at the 3‐year time point, intensive SBP control was associated with a significantly lower risk of MACE (hazard ratio [HR] 0.55, 95% CI, 0.32–0.95) using the IPTW Cox model. The associations remained consistent across multivariable Cox regression model (HR 0.53, 95% CI, 0.31–0.90) and overlap weighting model (HR 0.55, 95% CI, 0.32–0.94). Patients in the intensive SBP control group showed a trend toward lower recurrent stroke risk, though it was not statistically significant (HR 0.65, 95% CI, 0.30–1.37). Similar trends were observed in subgroup analyses. In conclusion, targeting an SBP below 120 mmHg in patients with diabetes and prior stroke is associated with a lower risk of major cardiovascular events without increasing the risk of recurrent stroke. Trial Registration: ClinicalTrials.gov identifier: NCT00000620